1997
DOI: 10.1016/s0893-133x(97)00085-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the 5-HT3 Antagonist, Ondansetron, on the Behavioral and Physiological Effects of Pentagastrin in Patients with Panic Disorder and Social Phobia

Abstract: Pentagastrin, a cholecystokinin (CCK) agonist, produces anxiety and panic in patients with panic disorder and social phobia. Preclinical data suggests that pentagastrin-induced anxiogenesis may be mediated via 5-HT3 receptors. In the present study, 14 patients with panic disorder or social phobia underwent pharmacological challenge in three conditions: (1) pretreatment with saline followed by pentagastrin infusion; (2) pretreatment with ondansetron followed by pentagastrin infusion; and (3) pretreatment with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…5-HT 3 receptor antagonists now from quiet long time are being practiced pre-clinically for its antidepressant-like effect (Ramamoorthy et al, 2008;Ramamoorthy and Radhakrishnan, 2010). Few clinical studies also employed 5-HT 3 receptor antagonists in several neuropsychiatric disorders (Israili, 2001;Wolf, 2000;McCann et al, 1997). Interstingly, 5-HT 3 receptor antagonists like ondansetron, LY-278584 and tropisetron have shown to regulate the plasma glucose level in various assays (Carvalho et al, 2005;Heimes et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…5-HT 3 receptor antagonists now from quiet long time are being practiced pre-clinically for its antidepressant-like effect (Ramamoorthy et al, 2008;Ramamoorthy and Radhakrishnan, 2010). Few clinical studies also employed 5-HT 3 receptor antagonists in several neuropsychiatric disorders (Israili, 2001;Wolf, 2000;McCann et al, 1997). Interstingly, 5-HT 3 receptor antagonists like ondansetron, LY-278584 and tropisetron have shown to regulate the plasma glucose level in various assays (Carvalho et al, 2005;Heimes et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, the highest dose of pentagastrin was close to inducing an 400 Bradwejn et al 1991;van Megen et al 1994;BrawmanMintzer et al 1997;McCann et al 1997a;van Vliet et al 1997).…”
Section: Plasma Levels Of Glucose Lactate and Cortisolmentioning
confidence: 95%
“…In that study (Bradwejn et al 1992), different doses of CCK4 were compared in patients with panic disorder showing that fixed doses higher than 15 µg (regardless of bodyweight) are panicogenic in 64-75% of the subjects. Pentagastrin has been documented to induce panic attacks (Abelson et al 1991van Megen et al 1994;Lines et al 1995;de Leeuw et al 1996;Brawman-Mintzer et al 1997;McCann et al 1997aMcCann et al , 1997b in doses from 0.2 µg/kg. Thus, in a normal adult weighing 70 kg, the dose of pentagastrin capable of inducing a panic reaction would be around 14 µg.…”
Section: Plasma Levels Of Glucose Lactate and Cortisolmentioning
confidence: 99%
“…Studies with 5-HT-ergic agents have shown that administration of dFEN tended to inhibit 7% CO 2 panic challenge (Mortimore and Anderson, 2000), while mixed 5-HT2A/2C and 5-HT1B/D receptors antagonist metergoline increased the anxiogenic response to 35% CO 2 inhalation in healthy subjects (Ben-Zion et al, 1999). An antagonist of 5-HT3 receptor ondansetron attenuated CCK-4-induced panic attacks acutely, but not after chronic treatment in healthy volunteers (Depot et al, 1999), and did not prevent the panicogenic effects of CCK-4 analog pentagastrin in patients with PD (McCann et al, 1997).…”
Section: Challenge Studiesmentioning
confidence: 99%